Case Report: Identification and Functional Analysis of a Homozygous Synonymous Variant in the PLOD1 Gene in a Chinese Neonatal With the Ehlers–Danlos Syndrome - Yan, Xiaodan; Shu, Jianbo; Nie, Yanyan; Zhang, Ying; Wang, Ping; Zhou, Weiwei; Cui, Xiaoyu; Liu, Yang (Frontiers in Pediatrics, 2022)
Background: The kyphotic type of Ehlers-Danlos syndrome (EDS ⅥA; OMIM225400) is a rare autosomal recessive genetic disease caused by variants in the PLOD1 gene. This research was to verified the disease-causing gene in a Chinese neonatal family with the Ehlers-Danlos syndrome. Methods: We r recruited a Han Chinese neonate with PLOD1-related kyphoscoliotic Ehlers-Danlos syndrome without kyphoscoliosis. Whole exome sequencing was conducted by the proband and Sanger sequencing was performed on all family members to confirm the variants. The variants site was predicted affecting splicing by NetGene2 Server and Alternative Splice Site Predictor (ASSP). We further conducted reverse transcription PCR and quantitative real-time PCR on all family members to verify that the synonymous variant affected splicing function. Results: A homozygous synonymous variant, c.1095C > T (p.Gly365=) in the PLOD1 gene was found and verified in the family with kyphotic Ehlers-Danlos syndrome. This variant resulting in premature termination codon of exon 10 affect the expression of the four bases GCGC. The expression level of qPCR in the proband was impaired, indicating that the variant affected mRNA splicing and protein function. Conclusion: Our research verified a homozygous synonymous variant in a Chinese neonatal family, which contributed to a better understanding of the molecular pathogenesis of PLOD1.